DAMPAK COVID-19 TERHADAP KEGIATAN PEMBELAJARAN ONLINE DI SEBUAH PERGURUAN TINGGI KRISTEN DI INDONESIA - Ericha Windhiyana (Perspektif Ilmu Pendidikan, 2020)
COVID-19 is an outbreak of disease originating from China which spread rapidly throughout the world. COVID-19 spread in Indonesia in early March 2020. The spread of this virus caused losses to several countries, especially in the field of economic. In the field of education, it also changed the learning model drastically; all learning activities are carried out online starting from elementary school level to university level. This research is a qualitative descriptive study describing online learning activities at a Christian university after the stipulation of all learning activities carried out from home in online mode. Interview was used to collect the data from 3 students and 2 lecturers. Based on the interview results, online learning activities at this university have been effective by utilizing the Zoom, Google Classroom, Schoology, and Edmodo applications. Constraint in implementing online learning mostly is internet connection problems that less supportive.